(untitled) (Journal of the College of Basic Education, 2022)
Some new β-Lactam and tetrazol derivatives were prepared from Schiff bases which the reaction of different substitution aromatic aldehyde with urea followed by cycloaddition reaction with chloroacetyl chloride and triethylamine to give β-Lactam .while reaction Schiff base with sodium azide give tetrazole . Also prepare bis lactam and tetrazol from the reaction of substitution aromatic acid with thionyl chloride to give substituted aromatic acid chloride followed by reaction with urea to give amide which followed cycloaddition reaction with chloroacetyl chloride and triethylamine to give bis β-Lactam .while reaction amid with sodium azide give bistetrazole .